Clinico-epidemiological profile of COVID-19 patients admitted during third wave of pandemic in a tertiary care hospital in New Delhi, India - Agrawal, Shreyash; Nath, Ravindra; Ish, Pranav; Gupta, Neeraj Kumar; Gaind, Rajni; Kale, Suniti; Gera, Rani; Dabral, Anjali; Gupta, Nitesh; COVID 2019 working group, *Other members of the Safdarjung Hospital (Monaldi Archives for Chest Disease, 2022)
Even nearly two years after the first reported case, the novel coronavirus (SARS-CoV-2) continues to ebb and flow around the world. A retrospective cohort study was carried out to determine the clinico-epidemiological profile and outcome of the cases. The study analyzed secondary data from 827 patients who presented to our center with COVID-19-related illnesses between December 15, 2021, and February 15, 2022 (third wave in India). There was a significant difference in the vaccination status of patients treated at home and those admitted, with 87.9% having received two doses compared to 74% in the second group being unvaccinated. Patients who were isolated at home recovered at a rate of 99.4%, while hospitalized patients died at a rate of 26.5%. Vaccination reduces the severity of COVID-19; however, constant vigilance for new variants, precautionary measures, and increased vaccination drives are critical moving forward. *Other members of the Safdarjung Hospital COVID-19 working group: B. Lal (Medicine), Harish Sachdeva (Anaesthesiology), Santvana Kohli (Anaesthesiology), Amandeep Jaswal (Anaesthesiology), Sumitra Bachani (Obstetrics and Gynecology), Ajay Kumar (Pediatrics), Rohit Kumar (Pulmonary Medicine), Vidya Sagar Chaturvedi (Surgery), Vinod Chaitanya (Medicine).